Partisipasi Masyarakat Terhadap Pencegahan Politik Uang Dalam Pemilihan Kepala Daerah di Kabupaten Belu Pada Tahun 2020: Studi Kasus Kabupaten Belu - Abdul Rahman Osama Djawas; Saryono Yohanes; Cyrilius W.T. Lamataro (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Election or General Election is a facility of freedom or right owned by the people to elect members of the House of Representatives, DPRD, DPD, President and Vice President which is carried out directly, publicly, freely, secretly, honestly and fairly or commonly abbreviated as LUBER JURDIL based on Pancasila of the Constitution of the Republic of Indonesia in 1945. There are various ways to win the hearts of the public in the implementation of elections, including through democratic strategies such as using the vision, mission, program and work of the candidate pair to the community. There are also other ways that are often done, even as if it is mandatory to be able to win elections, then for most voters it becomes a common and inevitable thing, namely money politics. The practice of using money in politics in Indonesia is not a new money. The reason is that from the reform period, the practice of money politics was rampant. Many candidate pairs use money as a way to bring victory in elections. This research is an empirical research supported by a qualitative descriptive approach that uses primary data and secondary data collected using interview and observation methods and data is processed using data examination methods (editing), data marking (coding), data validation, and data vertification and analyzed using judicial analysis techniques. The results of this study show that (1) The management of village funds by the Oelnaineno village government in meeting the community's needs for clean water has been carried out in accordance with procedures and gradually, this is marked by the creation of mini reservoirs and reservoirs in each hamlet. (2) Factors that affect the Oelnaineno village government in allocating village funds to fulfill the rights of the Oelnaineno village community to clean water, namely legal factors, law enforcement factors, facilities or facilities factors and community factors that are less active in taking part in helping the village government.